RATIONAL MAINTENANCE OF GAS PUMPING UNITS AT THE COMPRESSOR STATION OF AN UNDERGROUND GAS STORAGE - Bodnar, V. M.; Sadlivskyi, V. I.; Stasiuk, R. B. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2025)
A mathematical model for determining the reliability of a compressor unit based on the simplest failure rate is obtained, shown and considered on a practical example, a methodology for predicting the technical condition of the machine and based on technical diagnostics with the aim of ensuring the specified reliability. Based on mathematical modeling of the optimization process of servicing piston gas pumping units in the conditions of compressor stations of underground gas storage facilities, the dependences of the influence of production factors on the power and efficiency of the unit were obtained, which allow us to determine the rational operating modes of piston gas pumping units in the conditions of compressor stations, which made it possible to propose a methodology for selecting rational operating modes of piston gas pumping units. The objective function of increasing the efficiency of operation of piston gas pumping units when conducting parametric diagnostics of the compressor cylinder was constructed and the permissible energy losses and the maintenance interval for the components of the cylinder cavity of the compressor cylinder were determined.